Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1038/sj.jea.7500069
|View full text |Cite
|
Sign up to set email alerts
|

Determination of exposure to environmental tobacco smoke in restaurant and tavern workers in one US city

Abstract: Approximately 173 subjects employed as waiters, waitresses, or bartenders in the Knoxville, TN, Standard Metropolitan Statistical Area collected a sample of air from their breathing zone while at their workplace for one shift. In addition, area samples were placed near the work spaces of many of the subjects. Collected samples were analyzed for respirable suspended particulate matter ( RSPM ) , ultraviolet -absorbing and fluorescing particulate matter, solanesol, 3 -ethenyl pyridine ( 3 -EP ) , and nicotine. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 13 publications
4
39
1
3
Order By: Relevance
“…Mean values for combustion-derived particulate matter between 26 and 67 mg/m 3 have been reported in US studies (Crouse et al, 1988;Crouse and Carson, 1989;Ogden et al, 1990). Mean values of 29.4 mg/m 3 for combustion aerosol and 20.4 mg/m 3 for Sol-PM were reported in US restaurants (Maskarinec et al, 2000). The mean UVPM and FPM values found in this study are similar to those reported by Maskarinec, but the Sol-PM is somewhat lower.…”
Section: Particulate Matter Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Mean values for combustion-derived particulate matter between 26 and 67 mg/m 3 have been reported in US studies (Crouse et al, 1988;Crouse and Carson, 1989;Ogden et al, 1990). Mean values of 29.4 mg/m 3 for combustion aerosol and 20.4 mg/m 3 for Sol-PM were reported in US restaurants (Maskarinec et al, 2000). The mean UVPM and FPM values found in this study are similar to those reported by Maskarinec, but the Sol-PM is somewhat lower.…”
Section: Particulate Matter Resultssupporting
confidence: 79%
“…Means of 3.1-4.5 mg/m 3 (Moschandreas and Vuilleumier, 1999) and 6.0 mg/m 3 (Maskarinec et al, 2000) were reported in smoking sections of US restaurants. Mean nicotine levels of 14.8 mg/m 3 (Muramatsu et al, 1987) (Meger et al, 2000), and 0.4-46 mg/m 3 averaged at 7.0 mg/m 3 (Hyva¨rinen et al, 2000) have been published.…”
Section: Nicotine Resultsmentioning
confidence: 99%
“…Moreover, restaurant and bar wait-staff and bartenders are exposed to concentrations of indicators of ETS that are at least as high as those for people in other smoking-permitted workplaces (Jenkins and Counts, 1999). Bartenders and bar wait-staff are exposed to the highest concentrations of indictors of ETS among hospitality workers (Jenkins and Counts, 1999;Johnsson et al, 2003), and bartenders that work in a single room bar are exposed to approximately 10 times more of the indicators of ETS than those that work in larger, multiroom bars (Maskarinec et al, 2000). In an additional study, employees working in the gaming areas in casinos were determined to be exposed to indicators of ETS at levels that were greater than those observed in a representative sample of the US population (Trout et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Results of at least one workplace study (Maskarinec et al, 2000 ) -albeit in much different environments -have indicated poor agreement between individual personal monitor concentrations of ETS and those collected from nearby stationary area samplers, but good agreement between pooled data sets. For this study, when the data set is taken as a whole, median personal exposure concentrations were in good agreement with median area concentrations.…”
Section: Jenkins Et Almentioning
confidence: 99%
“…Analytical chemical procedures used in this study were identical to those used in our previous studies (e.g., Jenkins et al, 1996;Maskarinec et al, 2000 ). Vapor phase samples were analyzed for nicotine and 3 -EP, according to the method of Ogden (1991 ).…”
Section: Analysis Of Indoor Air and Ets Componentsmentioning
confidence: 99%